Phosphorus-reducing technologies in swine production - Boland, Michael A.; Foster, K.A.; Preckel, P.V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Soil phosphorus levels have increased as swine production has become concentrated. Phosphorus-based manure management regulations for land application have been proposed by policy makers. The objective of this research was to determine benefits/costs of adopting phytase for reducing phosphorus. Results were derived using different manure storage and application systems. Although phytase was a least-cost ingredient, it became profitable when producers were constrained by land. Land requirements were 2 to 5 times greater under a phosphorus application regulation than a nitrogen application regulation.
Keywords: Swine; Management; Manure; Nitrogen; Phosphorus; Phytase